Content and organisational forms of vocational training of gifted students in the belles lettres - Boiarska-Khomenko Anna; Naumenko Stanislav (Науковий Вісник Південноукраїнського Національного Педагогічного Університету імені К. Д. Ушинського, 2024)
The development of industry, digital technologies, the economy, science and culture, as well as the increase in labour mobility, requires an increase in the number of skilled workers capable of creative thinking and generating new ideas. Despite the fact that the modern labour market demonstrates a demand for blue-collar jobs, vocational education has lost its prestige in Ukraine and other countries. One of the reasons for this is the imperfection of the vocational education system in schools, in particular the insufficient involvement of gifted students in acquiring professional competences in various fields. In this context, it is interesting to study the experience of vocational training of children in China, which has a developed system of vocational education that prepares young people for the requirements of the labour market. The purpose of this study is to summarise the content, forms and methods of vocational training of gifted students in the PRC. The study used general scientific methods, such as analysis, synthesis, comparison and generalisation of knowledge in the fields of philosophy, psychology, pedagogy and cultural studies. Scientific, educational and methodological literature and official documents were analysed to determine the system and methods of vocational training in China. The results of the study showed that the education system in China has undergone reforms aimed at the individual development of gifted students. The main tasks of the Chinese school curriculum are to combine the content of education with technological progress and students’ life experience, develop practical skills, adapt the content of education to social needs, and ensure individual development and active learning. The Chinese system also includes the development of curricula that meet regional needs and the provision of free choice of subjects by students. China uses two main models of vocational training for gifted students: accelerated and enriched learning. Accelerated learning allows students to avoid limitations by adapting education to their abilities. It includes early enrolment, promotion to a higher grade, special classes and shortened programmes. Enriched learning, on the other hand, allows gifted students to study in regular classes with additional teacher support. This approach involves differentiated teaching, multi-level assignments, and the use of creative and problem-based tasks. China also uses elements of dual education, when gifted students work at enterprises under the enterprise-school model. China’s experience in vocational training of gifted students shows the importance of integrating education with the needs of the labour market, adapting curricula to regional characteristics, and ensuring an individual approach to learning. These approaches can be used to improve the vocational education system in other countries.